2021
DOI: 10.1093/bib/bbaa373
|View full text |Cite
|
Sign up to set email alerts
|

HISNAPI: a bioinformatic tool for dynamic hot spot analysis in nucleic acid–protein interface with a case study

Abstract: Protein–nucleic acid interactions play essential roles in many biological processes, such as transcription, replication and translation. In protein–nucleic acid interfaces, hotspot residues contribute the majority of binding affinity toward molecular recognition. Hotspot residues are commonly regarded as potential binding sites for compound molecules in drug design projects. The dynamic property is a considerable factor that affects the binding of ligands. Computational approaches have been developed to expedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The HISNAPI method predicts the impact of mutations at specific residues on the overall protein-RNA binding affinity and uses these values to identify the hotspots (Mei et al, 2021). Based on the strategy of computational alanine scanning, HISNAPI can quantitatively evaluate the changes in binding affinity between protein and RNA interactions.…”
Section: Hisnapimentioning
confidence: 99%
“…The HISNAPI method predicts the impact of mutations at specific residues on the overall protein-RNA binding affinity and uses these values to identify the hotspots (Mei et al, 2021). Based on the strategy of computational alanine scanning, HISNAPI can quantitatively evaluate the changes in binding affinity between protein and RNA interactions.…”
Section: Hisnapimentioning
confidence: 99%
“…mmCSM-NA [ 9 ] adapts the well-proven graph-based signature concept based on mCSM-NA and is the first scalable method capable of quantitatively and accurately predicting the effect of multipoint mutations on nucleic acid binding affinity. HISNAPI [ 10 ] takes into account the flexibility of protein-nucleic acid complexes by sampling conformations using molecular dynamics simulation, and using empirical force field FoldX to determine the binding energy of wild-type and mutant protein-nucleic complexs. The other is based on machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Protein–nucleic acid interactions (PNIs) are essential for several fundamental biological processes involving replication, transcription, and translation (Hoffman et al, 2004; Mei et al, 2021; Rigden & Fernández, 2021). With 20,500 proteins coding for genes by humans, they confirmed that 7.5% are linked to RNA metabolism through the binding and processing of RNA or forming significant parts of RNPs (Gerstberger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%